Development of Didactic Analysis Competence in Prospective Mathematics Teachers - Bethzabe Cotrado; María Burgos; Pablo Beltrán-Pellicer; Alfredo Carlos Castro (REDIMAT)
In this article, we describe the implementation and results of a formative experience with prospective mathematics teachers, focused on developing the competence for didactic-mathematical analysis of curriculum materials, specifically student workbooks related to probability. The research design follows a methodological approach typical of design-based research, utilizing content analysis to examine participants' responses. The study was conducted with 16 Peruvian students preparing to become mathematics teachers at the National University of the Altiplano. The responses from the prospective teachers revealed deficiencies in their common content knowledge. They also encountered difficulties in distinguishing mathematical practices and recognizing the mathematical objects involved in the study process, especially propositions and their respective arguments. Furthermore, they struggled to differentiate between intuitive, classical, and frequentist meanings of probability. To improve these outcomes, it is necessary to reinforce didactic-mathematical knowledge regarding probability.